Profil Peresepan Obat Peyakit Diare pada Pasien Rawat Inap Anak di RSU Dr. Kanujoso Djatiwibowo Balikpapan - Yullia Sukawaty; Rusdiati Helmidanora; Fitri Handayani (Jurnal Ilmu Kesehatan, 2017)
Diarrhea is one of the leading causes of death especially in children. Approximately 10% of cases of diarrhea in children under five years old (toddlers) worldwide are bloody diarrhea or dysentery.The purpose of this study was to determine profile of the diarrhea prescribing of children inpatients at hospital Dr. Kanudjoso Djatiwibowo Balikpapan period October to December 2015.This research was conducted by non experimental retrospectively method with purposive sampling and analyzed descriptively using microsoft excel.Profile of the diarrhea prescribing of children inpatients at hospital Dr. Kanudjoso Djatiwibowo Balikpapan encompasses the use of the single most antibiotic ceftriaxone 24%, the most commonly used combination antibiotic, ampicillin combination with chloramphenicol 12%, rehydration therapy widely used lactate ringer 38%, supplement therapy widely used zinc 90%.Prescribing medication for diarrheal disease of inpatients at hospital Dr. Kanudjoso Djatiwibowo Balikapapan has been in accordance with the procedure of diarrhea treatment of Ministry of Health RI (MOH RI 2011) five steps to solve diarrhea.